Contemporary Students’ Attitude to Traditional (Printed) Textbooks - Martišauskienė, Elvyda (Acta Paedagogica Vilnensia, 2006)
Life-long learning, as a key challenge of the 21st century, is changing attitude to all components of education process. The aim of the article is to discuss students’ attitude to traditional teaching and learning material, i.e. textbooks, in two aspects: their contemporarity and accessibility. 82% of university students and 73.9% of college students use textbooks often and very often. However, only one third (32.9%) of students are satisfied with their contemporarity for only such proportion of textbooks meet the study programmes. A special attention should be paid to part-time students’ provision with textbooks meeting the study programmes since only one fifth of them use textbooks. However, this form of study in the context of life-long learning is promising. Only one third (32.9%) of the textbooks have been printed in the last 5 years. According to the students’ opinion, exactly the same proportion of textbooks satisfies the requirements of study programmes. Such precise coincidence of the data cannot be accidental and raises the problem of textbooks’ suitability. Moreover, a bigger number of new textbooks are available in younger higher education institutions (in colleges and Vytautas Magnus University). University students have a more favourable attitude to textbooks prices. The fact that attitudes to prices vary with different institutions may be caused by accidental and situational factors. The research data allows for conclusion that attitude to prices of studies are mainly affected by social factors. The present situation regarding contemporarity and accessibility of printed textbooks can be solved integrating efforts of lecturers, university administrations and publishing houses.